Vom Holz : Holzdrucke der Gegenwart. - Gercken, Günther; Krajewski, Michael (Melsungen : B. Braun Melsungen AG, 1989)
Auberger, Pidder ; Büttner, Werner ; Droese, Felix ; Kiecol, Hubert ; Kluge, Gustav ; Mansen, Matthias ; Modersohn, Heinrich
Duits
boek